Eiropas Savienības Tiesas prejudiciālo nolēmumu izmantošana Latvijas Republikas Satversmes tiesas praksē - Zariņa, Roberta (Latvijas Universitāte, 2025)
Līguma par Eiropas Savienības darbību 267. pantā paredzētā prejudiciālā nolēmuma procedūra nesniedz skaidru tās jēdzienu un to vai konstitucionālās tiesas arī var vērsties Eiropas Savienības Tiesā. Maģistra darbā “Eiropas Savienības Tiesas prejudiciālo nolēmumu izmantošana Latvijas Republikas Satversmes tiesas praksē” tiek sniegts ieskats konstitucionālo tiesu nozīmē LESD 267. panta izpratnē, ES dalībvalstu attieksmē prejudiciālo nolēmumu lūgšanā un visbūtiskāk - pētīta Satversmes tiesas mijiedarbība ar ES Tiesu prejudiciālā nolēmuma procedūrā detalizēti analizējot visas lietas kurās līdz šim Satversmes tiesa ir vērsusies ES Tiesā. Analizēti nacionālā tiesiskā regulējuma problemātika un politiskā nostāja, kas ietekmē Satversmes tiesas aktivitāti, kura pēdējo gadu laikā ir pieaugusi.

The preliminary ruling procedure provided in Article 267 of the Treaty on the Functioning of the European Union does not provide a clear definition of its meaning and whether constitutional courts may also apply to the Court of Justice of the European Union. In the Master thesis “The use of a preliminary ruling by the Court of Justice of the European Union in the practice of the Constitutional Court of the Republic of Latvia” is provided to the Constitutional Court within the meaning of Article 267 TFEU, the attitude of the EU Member States in the request for preliminary rulings and, most importantly, the interaction of the Constitutional Court with the Court of Justice of the European Union in the preliminary ruling procedure by analysing in detail all cases in which the Constitutional Court has brought an action before the Court of Justice of the European Union so far. There is an analysis of the problem of national legal frameworks and the political stance affecting the activity of the Constitutional Court which has grown over the past few years.
The use of preliminary rulings of the Court of Justice of the European Union in the practice of the Constitutional Court of the Republic of Latvia
Keywords: Juridiskā zinātne; LESD 267. pants, Article 267 TFEU; prejudiciāls nolēmums, preliminary ruling; konstitucionālā tiesa, Constitutional Court; Satversmes tiesa, Constitutional Court of Republic of Latvia; Eiropas Savienības Tiesa, Court of Justice of the European Union